Active screening significantly improves detection of chlamydia in women’s health clinics in Shaoxing, China - Jieqiong Guan; Jie Feng; Lingying Zhu; Jinlong Ding (PLoS ONE, 2025)
Background Chlamydia trachomatis (CT) infection is one of the most prevalent genital tract infections which has been reported to have adverse effects on reproductive health. However, doctors will only test for CT infection if there are associated symptoms. This study aimed to compare outcomes before and after implementing a CT screening protocol to evaluate whether to encourage more routinized CT screening. Methods A hospital-based survey was conducted at Shaoxing Maternity and Child Health Care Hospital. The study was divided into two time periods, T1 (July 2021–June 2022, before screening protocol) and T2 (July 2022–June 2023, after screening protocol). The study included females aged over 16 years who agreed to CT testing at four clinics, including obstetrics, infertility, termination of pregnancy and gynecology. The nucleic acid amplification results were utilized to ascertain the presence of chlamydia infection in cervical secretions. Results After active promotion of CT screening, 15,005 females were tested, with an average age of 32.2 years (SD = 8.3), which were more than double the previous number and significantly younger (P < 0.05). Significant differences in the number of people CT screened were observed in the obstetrics (2.5%–66.5%, P < 0.05) and termination of pregnancy (7.5%–45.3%, P < 0.05) clinics. The positive rates of CT in T1 and T2 were 6.8% (491/7230) and 5.2% (774/15005), respectively. The implementing chlamydia screening identified an additional 184 (11–195) infected pregnant women in obstetrics clinics (a similar number of outpatient visits). The age group with the highest proportion was 26–30 years (27.6%), followed by 21–25 years (21.4%) and 31–35 years (21.1%). Conclusions Active screening significantly improves the detection of chlamydia in women's health clinics. Pregnant individuals and those seeking pregnancy termination were previously overlooked in CT screening efforts but required increased attention.